Career Decision-Making Self-Efficacy among Undergraduate Students in Collectivistic Contexts: A Scoping Review - rahayu, euis; Widayanti, Costrie Ganes; Sawitri, Dian Ratna (Universitas Ahmad Dahlan, 2024)
Career decision-making self-efficacy is the level of individual confidence in successfully making career decisions and is characterized by the ability to conduct self-assessments, gather information about one’s career, select goals, make plans, and solve problems. The purpose of this study is to describe career decision-making self-efficacy in students in a collectivistic culture, both in the form of internal and external factors that influence each other, so that it has an impact on a person’s career decision-making self-efficacy. This research method used the scoping review method. A systematic review was conducted with online databases, namely, Scopus, Springer, EBSCO, ProQuest, and Emerald Insight, using predetermined keywords. Then, the articles were filtered based on the inclusion and exclusion criteria so that 7 articles met the eligibility criteria for analysis and were published between 2013 and 2023. The findings of this study indicate that in a collectivistic culture, family influence and support affect the formation of internal factors in the form of emotional regulation both adaptively and maladaptively. Family influence and support also influence career adaptation, self-awareness, career search skills, campus life adaptation, academic satisfaction, work experience, personality, future perspectives, and self-competence, and these factors lead to high career decision-making self-efficacy.